Identification of Tetraspanin-7 as a Target of Autoantibodies in Type 1 Diabetes - McLaughlin, Kerry A; Richardson, Carolyn C; Ravishankar, Aarthi; Brigatti, Cristina; Liberati, Daniela; Lampasona, Vito; Piemonti, Lorenzo; Morgan, Diana; Feltbower, Richard G; Christie, Michael R (Diabetes (New York, N.Y.), 2016)
The presence of autoantibodies to multiple-islet autoantigens confers high risk for the development of type 1 diabetes. Four major autoantigens are established (insulin, glutamate decarboxylase, IA2, and zinc transporter-8), but the molecular identity of a fifth, a 38-kDa membrane glycoprotein (Glima), is unknown. Glima antibodies have been detectable only by immunoprecipitation from extracts of radiolabeled islet or neuronal cells. We sought to identify Glima to enable efficient assay of these autoantibodies. Mouse brain and lung were shown to express Glima. Membrane glycoproteins from extracts of these organs were enriched by detergent phase separation, lectin affinity chromatography, and SDS-PAGE. Proteins were also immunoaffinity purified from brain extracts using autoantibodies from the sera of patients with diabetes before SDS-PAGE. Eluates from gel regions equivalent to 38 kDa were analyzed by liquid chromatography-tandem mass spectrometry for protein identification. Three proteins were detected in samples from the brain and lung extracts, and in the immunoaffinity-purified sample, but not in the negative control. Only tetraspanin-7, a multipass transmembrane glycoprotein with neuroendocrine expression, had physical characteristics expected of Glima. Tetraspanin-7 was confirmed as an autoantigen by demonstrating binding to autoantibodies in type 1 diabetes. We identify tetraspanin-7 as a target of autoimmunity in diabetes, allowing its exploitation for diabetes prediction and immunotherapy.